Chromone–indanedione reactant: a bifunctional 3C synthon for diastereoselective construction of skeleton-diversified bispiro-[chromanocyclopentane-oxindole-indanedione]. (30th June 2021) - Zhou, Wei; Li, Zheng; Tian, You-Ping; Han, Xiao-Xue; Liu, Xiong-Li
Abstract : A new type of bifunctional 3C synthon, a chromone–indanedione precursor, was employed for diastereoselective Michael/Michael cycloaddition with methyleneindolinones to generate a series of potentially bioactive bispiro-[chromanocyclopentane-oxindole-indanedione] frameworks with skeletal diversity in a single operation. Abstract : A new type of bifunctional 3C synthon, a chromone–indanedione precursor, was employed for diastereoselective Michael/Michael cycloaddition with methyleneindolinones to generate a series of potentially bioactive bispiro-[chromanocyclopentane-oxindole-indanedione] frameworks with skeletal diversity in a single operation. This reaction exhibited good substrate tolerance and gave the desired products in moderate to good yields with high diastereoselectivities via an endo -transition state (up to 78% yield and >20 : 1 diastereomeric ratio). In particular, this reaction is the first example of using a chromone–indanedione precursor as a bifunctional 3C synthon, the first example of the construction of bispiro-chromanocyclopentanes, and also the first example of the introduction of a chromanocyclopentane moiety into spiroindanone frameworks, which might be valuable in medicinal chemistry.